Sirolimus for the Treatment of Airway Obstruction due to Indolent T-Lymphoblastic Proliferation - Eric Moughames; Ana P. Kiess; Lee M. Akst; Antoine Azar (Case Reports in Immunology)
Introduction. Indolent T-lymphoblastic proliferation (iT-LBP) is a rare nonmalignant entity that presents as a proliferation of T-lymphoblasts. We report a first such case with a recurrent laryngeal obstruction presentation that was successfully controlled with Sirolimus. Case presentation. This is the case of a 29-year-old female who presented with a recurrent significant lymphoid hyperplasia in the adenoid and tongue base region as well as a right cervical lymph node. After repeated adenoidectomies and tonsillectomies, and based on pathological and clinical findings she was diagnosed with iT-LBP. Trials of radiotherapy and immunotherapy with cyclosporine and rituximab all failed to control the progression of the disease. Sirolimus was finally able to restrict the growth and improve her symptoms. Conclusion. While It-LBP does not usually require treatment, it is important to report cases in which treatment was crucial for the survival of the patient, and the effective role of Sirolimus in doing so, without any major adverse effects.